Arbitrary Fixed-Time Sliding Mode Control for Buck Converter With Matched and Mismatched Disturbances Based on Fixed-Time Observer - Orhan Kaplan; Ferhat Bodur; Mustafa Bahadir Ozdemir (IEEE Access)
This article introduces an arbitrary fixed-time sliding mode controller based on the fixed-time disturbance observer (FxDO-FxSMC) for a buck converter with disturbance. FxDO-FxSMC is proposed to address the issues of finite time convergence and large initial conditions present in existing sliding mode controllers. FxDO-FxSMC uses an arbitrary sliding surface to stabilize the buck converter in the presence of both matched and mismatched disturbances while ensuring arbitrary fixed-time convergence. First, the buck converter’s modified state-space model, which contains both matched and mismatched disturbances, is defined. Secondly, an arbitrary fixed-time disturbance observer is designed to predict disturbances. Finally, an arbitrary FXSMC is constructed by defining the sliding surface with an arbitrary term and estimated mismatched disturbance. The FxDO-FxSMC method 1) tackles an arbitrary fixed time sliding surface for the buck converter with mismatched disturbance, a feature not achievable with the current finite/fixed time sliding mode control; 2) allows the user to adjust the convergence time of the proposed method, regardless of the initial conditions; and 3) concurrently mitigates chattering issues. Additionally, Lyapunov stability is carried out. To highlight the advantages of the proposed combined structure, it is compared with the classical SMC, integral SMC (ISMC), disturbance observer-based SMC (DO-SMC), and finite-time disturbance observer-based non-singular terminal SMC (FnDO-NTSMC). As a result of the simulation tests, the chattering rate value (CRV) has been enhanced by 36.19% according to FnDO-NTSMC, which provided the best response compared to other traditional techniques. The simulation results demonstrate that the proposed controller effectively reduces overshoot, steady state error, and response time compared to traditional and other controllers. We evaluated system performance using dynamic response MSE, RMSE, and MAE for fair comparison. DO-SMC outperformed existing approaches in RMSE and MAE; however, the proposed controller improved 174.27% and 99.26%. The simulation results prove that the proposed controller design exhibits more rapid convergence and dynamic response to disturbances, regardless of initial conditions.